The Inflammasome in Reproductive Biology: A Promising Target for Novel Therapies - de Rivero Vaccari, Juan Pablo (Frontiers in Endocrinology, 2020)
The inflammasome is a key regulator of innate immunity involved in the inflammatory response to infections as well as disease through the activation of caspase-1 and the processing of the inflammatory cytokines interleukin (IL)-1b and IL-18. Even though the inflammasome was first described in the context of infections, most research these days focuses on targeting the inflammasome as a therapeutic option in sterile inflammatory events. Recent evidence indicates a clear involvement of the inflammasome in topics related to reproduction as diverse as infertility and pre-eclampsia. Here I summarize the current findings on the inflammasome that have been described in the field of reproductive biology and highlight the potential that the inflammasome has to be considered as a therapeutic target as a novel option in this field.